Taxonomic update of Dryadella (Orchidaceae: Pleurothallidinae) based on morphometric analyses of three species of the Brazilian Atlantic rainforest - Imig, Daniela Cristina [UNESP] (2023)
Dryadella (Orchidaceae, Epidendreae) is a Neotropical genus predominantly distributed in the Andean region and the Atlantic rainforest (ARF). Three species occurring in the Brazilian ARF, Dryadella edwallii, D. wuerstlei, and D. zebrina, are challenge to tell apart due to the overlap of morphological characters that define them, so we considered these species as morphotypes. To evaluate the current taxonomic status and to identify suitable characters for the better delimitation of taxon within this group, we measured and analyzed 40 flower characters from 145 individuals of 23 populations distributed throughout the geographical range of this species complex, representing all the morphological diversity of these morphotypes. We performed a principal component analysis (PCA) to summarize all the morphological variations found and a permutational multivariate analysis of variance (PERMANOVA) to verify whether the groups formed by the PCA are statistically different. To assess the phenetic relationships among individuals, we generated an unweighted pair group method with arithmetic mean (UPGMA) dendrogram. As a result, it was possible to clearly differentiate D. wuerstlei from the two other species. The variables that contributed most to the differentiation of the species were the perimeter and area of the sepals (SD1, SD2, SL10); area and width of the apex, mid-portion, and base of the petals (PT19, PT21, PT22, and PT2); and the measurements of the base and widest portion of the lip blade (LB36, LB38). The second group was formed by all individuals of D. edwallii and D. zebrina which present highly overlapping characters with no clear separation between their populations based on PCA and UPGMA results. With this in view, we considered that D. edwallii and D. zebrina correspond to a single species, while D. wuerstlei should remain recognized as a distinct species. We present a taxonomic circumscription of D. wuerstlei and D. zebrina to clarify the taxonomic delimitation of these taxa, highlighting morphological diagnostic characters and their geographical distribution.